MARKETING CHANNEL ANALYSIS OF SKIPJACK TUNA (EUTHYNNUS AFFINIS) AT THE TENAU COASTAL FISHING PORT, KUPANG CITY (Jurnal Pembangunan Perikanan dan Agribisnis, 2026)
This study aims to analyze the marketing channels of skipjack tuna (Euthynnus affinis) at the Coastal Fishing Port (PPP) Tenau, Kupang City. The research focuses on identifying the types of marketing channels, marketing costs, marketing margins, and the efficiency of marketing. The study employs both qualitative and quantitative descriptive methods, with data collected through observation, interviews, questionnaires, and documentation. The sample consists of 54 respondents, including fishermen, collecting traders, and retail traders. The results indicate that during the high fishing season, there are two types of marketing channels: (1) Fishermen → Retailers → Consumers, and (2) Fishermen → Collecting Traders → Retailers → Consumers. During the low fishing season, only one channel is found: Fishermen → Collecting Traders → Retailers → Consumers. The marketing cost for Channel I is IDR 162.000, while for Channel II it is IDR 346.896. The highest marketing margin is found in the low season, particularly in Channel II. Based on efficiency calculations, all marketing channels show an efficiency value below 50%, indicating that the marketing of skipjack tuna at PPP Tenau is relatively efficient.